Gender and Fashion Style Choices in University Students - Inke Miladunka Rahma; Erna Herawati (Faculty of Social Science, Universitas Negeri Malang, 2024)
This article discusses the connection between gender and fashion style choices among university students. It highlights the role of socialization, enculturation, and internalization in shaping students' understanding of gender and their fashion preferences. Through a qualitative-phenomenological approach, the study explores the experiences of gender socialization among students and examines the relationship between gender and fashion choices. The findings indicate that there is no direct link between gender and students' fashion style preferences. However, fashion is viewed as a medium for expressing one's gender identity. The study finds that students exhibit flexibility in their fashion choices, adapting them to social contexts, specific events, and personal comfort. Nevertheless, the influence of gender socialization, enculturation, and internalization acquired since childhood is evident in their fashion decisions. Overall, the research emphasizes the complexity and individuality of students' fashion style choices within the broader context of gender.